2015
DOI: 10.1002/jps.24259
|View full text |Cite
|
Sign up to set email alerts
|

Do Not Drop: Mechanical Shock in Vials Causes Cavitation, Protein Aggregation, and Particle Formation

Abstract: Industry experience suggests that g-forces sustained when vials containing protein formulations are accidentally dropped can cause aggregation and particle formation. To study this phenomenon, a shock tower was used to apply controlled g-forces to glass vials containing formulations of two monoclonal antibodies and recombinant human growth hormone (rhGH). High-speed video analysis showed cavitation bubbles forming within 30 μs and subsequently collapsing in the formulations. As a result of echoing shock waves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 25 publications
(55 reference statements)
0
80
2
Order By: Relevance
“…In a previous study we showed that the influence of cavitation derived from a micro‐orifice reduced the monomeric content of human serum albumin (HSA) and enhanced dimeric HSA, whereas isolated shear rates of up to 10 8 s −1 had no influence on HSA aggregation behavior. Furthermore, we hypothesized that the main driving force for protein aggregation when cavitation occurs is most likely the increased vapor/liquid interface due to cavitation bubble formation and not the hydroxyl radical formation obtained from bubble collapse as previously described …”
Section: Introductionmentioning
confidence: 93%
“…In a previous study we showed that the influence of cavitation derived from a micro‐orifice reduced the monomeric content of human serum albumin (HSA) and enhanced dimeric HSA, whereas isolated shear rates of up to 10 8 s −1 had no influence on HSA aggregation behavior. Furthermore, we hypothesized that the main driving force for protein aggregation when cavitation occurs is most likely the increased vapor/liquid interface due to cavitation bubble formation and not the hydroxyl radical formation obtained from bubble collapse as previously described …”
Section: Introductionmentioning
confidence: 93%
“…Regulatory agencies place increased emphasis on the potential clinical implications of subvisible particles and recommend careful analysis to characterize the particles in therapeutic protein products . The precise mechanism by which subvisible particles form is unknown, but researchers consider freezing, oxidation, elevated temperatures, exposure to light, mechanical stress, stress during purification, production, storage and transport to be major contributing factors . Materials in contact with the product, such as the product vial components, can also affect particle formation .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The precise mechanism by which subvisible particles form is unknown, but researchers consider freezing, oxidation, elevated temperatures, exposure to light, mechanical stress, stress during purification, production, storage and transport to be major contributing factors. [13][14][15][16][17][18] Materials in contact with the product, such as the product vial components, can also affect particle formation. 17 Advances in analytical technologies have enabled quantification and examination of the morphology of these particles.…”
mentioning
confidence: 99%
“…caused through cavitation phenomena, can be as well induced by shock-waves, as seen for example in under water explosions [25]. Moreover, Randolph and co-workers [26] have recently reported that the mechanical shock in vials, i.e.…”
Section: Introductionmentioning
confidence: 99%